Developing School Culture through Transformational Leadership of the Principal at State Elementary School 167646, Padang Hilir District, Tebing Tinggi City - Dea Anisha; Nurika Khalila Daulay (Universitas Muhammadiyah Enrekang, 2024)
As the main leader in a school, the principal has a crucial role in building and developing a positive school culture. This study focuses on SDN 167646 in Padang Hulu District, Tebing Tinggi City. The approach used in this study is qualitative with descriptive methods. The main objective of this study is to analyze the development of school culture through the leadership of the principal at SDN 167646. By comparing the ideal conditions expected with the reality that occurs, this study is expected to contribute to improving the quality of education at the school. The results of the study indicate that the principal acts as a visionary leader, role model, cooperation facilitator, problem solver, and evaluator in forming a school culture that focuses on building student character, improving the quality of learning, and strengthening positive values. Although there are various challenges, such as resistance to change, budget constraints, and minimal parental involvement, the strategies implemented by the principal through a dialogic approach, teacher training, and cooperation with the community have succeeded in overcoming these obstacles. The resulting changes are seen in increased discipline, cooperation, and active participation of students in various school programs.